Psychological Foundations of Teaching Russian as a Foreign Language (Eurasian Journal of Learning and Academic Teaching, 2024)
This article is dedicated to the psychological foundations of teaching Russian as a foreign language. Key aspects affecting successful language acquisition are examined, including motivation, cognitive processes, emotional factors, social aspects, personality traits, and intercultural competence. Special attention is given to the importance of supporting both intrinsic and extrinsic motivation of students, considering their cognitive styles and emotional states, and creating a favorable educational environment. The significance of integrating cultural elements into the teaching process to develop intercultural competence is emphasized. Recommendations are provided for teachers to adapt methods and approaches according to the individual needs of students.